FAST FUZZY FORCE-DIRECTED/SIMULATED EVOLUTION METAHEURISTIC FOR MULTIOBJECTIVE VLSI CELL PLACEMENT - Sait, Sadiq M. (2006)
VLSI standard cell placement is the process of arranging circuit components (modules) on a silicon layout. The cell placement problem is a proven NP hard combinatorial optimization problem. The complexity of this problem increases when multiple optimization objectives are considered simultaneously. In this paper, a novel technique is presented to address this hard problem, while optimizing multiple objectives. A major difculty with such multi-objective combinatorial optimization problems is the existence of a very large solution search space, one of which is the desired optimal solution. Simulated Evolution (SE) a general iterative heuristic is used to traverse the large search space, while fuzzy logic is resorted to assist in multi-criteria decision making and overcome the imprecise nature of design information at placement stage. New fuzzy aggregation functions are proposed. SE is hybridized with force directed algorithm to speed-up the search. The proposed schemes are compared with previously presented SE based heuristics. The implementations exhibit considerable improvement in terms of both solution quality and runtime.